Assessment of the home ecosystem of elderly people with Alzheimer's from the Holistic Ecosystem Health Indicator - Ilha, Silomar (2020)
The objective was to reflect on the use, by nurses, of the Holistic Ecosystem Health Indicator, in order to contribute to the health of the home Ecosystem and care for the elderly with Alzheimer's disease. It is a descriptive study, reflective analysis type, developed through the reading of scientific articles and book chapters selected in the discipline of Doctorate: Nursing Work / Health and Socio-Environmental Context, of the Graduate Program in Nursing, Federal University of Rio Grande. The Derivation Theory with methodological support and an Ecosystem approach was used as a theoretical framework for reflection. The results are presented through two axes: Presentation of the Holistic Health Indicator of the home ecosystem of elderly people with Alzheimer's disease; Contribution of the Holistic Ecosystem Health Indicator to the home ecosystem of elderly people with Alzheimer's disease. It is concluded that the use of the Holistic Ecosystem Health Indicator, by nurses, can be an important tool in the assessment of the home ecosystem of elderly people with Alzheimer's disease, with a view to finding indicators of instability. The indicators can contribute to the implementation of a care plan directed to the needs of the home ecosystem, as a complex unit.